Reconstruction of aortal arch in patients with transposition of the main arteries: results of a one-stage correction - Ya. P. Truba; M. P. Radchenko; I. V. Dzyurii; O. S. Golovenko; V. V. Lazoryshynets (Клінічна хірургія, 2020)
Objective. To analyze immediate and late results of a one-stage surgical treatment of the main arteries transposition in conjunction with obstruction on the level of aortal arch.